Tinjauan Etika Kristen Terhadap Penerapan Hukuman Mati dalam Konteks Modern - Hurmanisa Hurmanisa; Grasela Sinta; Juan Andika Manuputty; Sarmauli Sarmauli (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The death penalty remains a topic of ongoing debate from legal, moral, and religious perspectives. In Indonesia, the death penalty is still applied for certain serious crimes; however, its implementation is questioned because it is considered to conflict with the fundamental human right to life. From the perspective of Christian ethics, this issue becomes more complex as it relates to the understanding of life as a gift from God and the principles of justice and forgiveness. The Old Testament contains provisions for the death penalty as a means of upholding law and maintaining the holiness of the community, while the New Testament emphasizes love, restoration, and the opportunity for repentance through the example of Jesus Christ. This study aims to analyze how Christian ethics views the death penalty by examining the balance between justice and forgiveness as taught in Scripture. The method used in this research is literature review and conceptual analysis of biblical texts and theological sources. The findings indicate that Christian ethics does not merely reject or accept the death penalty, but directs toward an understanding of justice that restores human dignity. This perspective is expected to serve as an ethical consideration in responding to the application of the death penalty in modern society.